Enhanced thermal conductivity of welding spots by coatings cupric acetate on copper nanoparticle solders. (29th May 2019) - Wu, Dongxu; Huang, Congliang; Ma, Yahui; Wang, Yukai; Wang, Fengchao; Guo, Chuwen
Abstracts: Applications of copper nanoparticle solders in low-temperature welding are much limited by copper oxidation because the oxidate could reduce the thermal conductivity in welding spots which could cause an overheating of electronic devices. In this work, a simple method was applied to prepare nanoparticles with cupric acetate coatings (CA-coatings) by using acetic acid to treat copper nanoparticles for enhancing thermal conductivities of welding spots. Effects of the CA-coating on thermal, electrical conductivities and chemical stability of copper nanoparticles were probed. Results turn out that CA-coating treatment of copper nanoparticles could enhance the thermal and electrical conductivities in welding spot, and the thermal conductivity in the welding spot can be enhanced about 30% compared to that for untreated copper nanoparticles. This coating could finally be recovered into copper in the welding process. Our experiments also show that the CA-coating copper nanoparticles have much higher chemical stability than untreated copper nanoparticles, when they are exposed in the atmosphere. This work provides a simple and effective way for increasing the thermal conductivity of welding spots and also supply some information for designing new soldering materials.